The Effectiveness of Multimodel-Based Physics Modules on Students’ Problem-Solving Ability - Stefany Amabel Putri; Abdul Salam M; Surya Haryandi (Jurnal Ilmiah Pendidikan Fisika, 2023)
Student problem-solving abilities refer to students' ability to identify problems, analyze problems, develop, and implement these solutions effectively. But in fact, this ability rarely gets attention in school. This study aimed to describe the effectiveness of the multimodel-based physics module on students' problem-solving abilities. This module was developed using Flip PDF Professional with the ADDIE development model and implemented in 34 students of class X MIPA at a high school in Banjarbaru. Data collection instruments were obtained from student learning outcomes based on problem-solving indicators. The results showed an increase in students' problem-solving abilities; this was based on the acquisition of a mean pre-test score of 4.63 in the very poor category to a post-test average score of 52.68 in the sufficient category and supported by an n-gain of 0.50 in the moderate category. Thus, it can be concluded that the multimodel-based physics module developed is classified as effective in improving students' problem-solving abilities.